Development and Evaluation of a Novel In-Clinic Automated Hematology Analyzer, ProCyte Dx, for Canine Erythrocyte Indices, Leukogram, Platelet Counts and Reticulocyte Counts - FUJINO, Yasuhito (The Japanese Society of Veterinary Science, 2013)
A novel hematology analyzer for small animal medicine, ProCyte Dx, was developed from combination of the fluorescence laser flow cytometry and laminar flow impedance technologies, and its accuracy was evaluated by comparing with the conventional impedance-based hematology analyzer, pocH-100iV Diff, or microscopic manual cell counting methods with staining blood smears in the canine blood. Blood samples of 59 dogs were hematologically analyzed and compared by Pearson’s correlation coefficients. Analyses between the two analyzers showed excellent correlation in RBC (r=0.998), HGB (r=0.999), HCT (r=0.998), MCV (r=0.994), MCH (r=0.974), MCHC (r=0.906), WBC (r=0.998) and PLT (r=0.993). Analyses between ProCyte Dx and microscopic manual counting results showed excellent correlation in neutrophils (r=0.920), lymphocytes (r=0.913) and reticulocyte percentages (r=0.924), good correlation in eosinophils (r=0.815) and reticulocyte numbers (r=0.850) and fair correlation in monocytes (r=0.770). The present study indicates that ProCyte Dx is acceptably accurate and can be a powerful tool for canine clinical medicine.